Assessing the Internal and External Factors Influencing Farmers’ Welfare - Daulika, Putri; Fahrunsyah, Fahrunsyah; Syakhril, Syakhril; Saleh, Muhammad; Karno, Karno; Setiawan, Maman (Journal of Agriprecision & Social Impact, 2025)
Farmer welfare is indicated by the level of purchasing power, which is calculated based on the ratio between the price index received from agricultural products and the price index paid for household consumption and production inputs. This study aims to analyze the internal and external factors influencing farmers’ welfare in Kutai Kartanegara Regency. The research data is primary and secondary data with a mixed method. The analysis was conducted using multiple linear regression to identify the factors that significantly affect farmers’ welfare. The results show that income, commodity prices, household consumption, and agricultural input costs are significant determinants of farmers’ welfare. Income and commodity prices have a positive effect, while agricultural input costs have a negative effect. The coefficient of determination (R²) values of 81.70% for the food crop subsector and 64.67% for the plantation subsector indicate that these variables explain a large portion of the variation in farmers’ welfare in the study area. Increased income increases welfare, but if consumption expenditure and input costs increase more than the increase in income, then farmer welfare will actually decrease. There is a need for policies to stabilize agricultural product prices, reduce production costs, and increase farmer productivity in Kutai Kartanegara Regency by strengthening market access, providing affordable inputs, and implementing technology and training so that agricultural products have added value and farmer welfare increases.